2019
DOI: 10.3126/jcmsn.v15i3.24642
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Outbreak Investigation of Chickenpox in Baidauli VDC, Nawalparasi, Nepal

Abstract: Background: On 2015, a cluster of chickenpox like symptoms was reported in Baidauli VDC of Nawalparasi, Nepal. This study aims to report the outbreak investigation and guide preventive and control measures. Methods: This investigation was conducted in Baidauli VDC of Nawalparasi, Nepal where a large number of cases with infectious rashes with fever was reported. Data were collected using a semi-structured questionnaire comprising of socio-demographic characteristics and clinical features. A detailed clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
(11 reference statements)
2
0
0
Order By: Relevance
“… 3 , 9 All our cases had a generalised rash which is similar to that reported by other studies. 3 , 13 Fever was reported in a majority of cases i.e 96.4% cases, 83% casses and 75% cases in three different studies done in similar setting which is similar to that reported in ours. 3 , 9 , 13 …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“… 3 , 9 All our cases had a generalised rash which is similar to that reported by other studies. 3 , 13 Fever was reported in a majority of cases i.e 96.4% cases, 83% casses and 75% cases in three different studies done in similar setting which is similar to that reported in ours. 3 , 9 , 13 …”
Section: Discussionsupporting
confidence: 89%
“… 3 , 13 Fever was reported in a majority of cases i.e 96.4% cases, 83% casses and 75% cases in three different studies done in similar setting which is similar to that reported in ours. 3 , 9 , 13 …”
Section: Discussionsupporting
confidence: 89%